Specialist Languages in Translation: The Case of Selected Expressions of Property Law - Selmistraitis, Linas; Gęborys, Katarzyna; Krawiec, Marek (Lingua Posnaniensis, 2018)
The concept of specialist languages has been widely discussed and analyzed not only with respect to the linguistic field (in the context of which certain changes are anticipated in language as a communicational tool), or translation studies (including cultural aspects of expressions and their equivalents) but also with respect to strategies and techniques used in the foreign language teaching process. The main objective of this paper is to examine the language of law on a sample of selected Polish legal expressions (property law expressions) and their English equivalents. The article points to the ways of translating expressions from this specialist language and emphasizes the need to include some cultural aspects in the translation process. The article starts with a presentation of various views on translation, and then provides information on specialist languages, their types and features, leading subsequently to the analysis of certain terms and concepts of law and the ways of translating them.